Study on occupational and nonoccupational risk factors and health of motor transport workers - Obelenis, Vytautas; Gedgaudienė, Daiva (Transport, 2003)
The study on work conditions, lifestyle, psychosocial factors and health was carried out in three different urban motor transport companies. 788 workers of the main occupations were interviewed using a questionnaire. The main occupational hazards are low air temperature, draughts, exposure to diesel fuel, cooling oil, noise, vibration, musculoskeletal exertion. Workers do not lead a healthy lifestyle: 46,0 %-are smokers, 83,0%-use alcohol, 53,0% are physically inactive, 82,0% lead a malnutrition regimen, 27,0% experience stressful situations at work every day. Musculoskeletal disorders make up 46,2%, respiratory 22,2%, gastrointestinal 17,3% and central nervous system dysfunction 32,2%. Musculoskeletal disorders are related to poor ergonomic and workplace design, long working hours, senior age and long professional work experience (p<0,05-0,002). First Published Online: 19 Dec 2011